2002
DOI: 10.1108/07363760210414943
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐channel shopping: understanding what drives channel choice

Abstract: Observes that traditional retail, catalog, and online‐only businesses face a critical decision – to accept a new, yet unrefined business model that includes multiple channels or to retain their single channel model and risk becoming obsolete and left behind by new, multi‐channel competitors. The decision process and implementation of a multi‐channel strategy could be simplified if businesses understood what drives consumers to a single channel, multiple channels, and which channels are preferred. Outlines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(191 citation statements)
references
References 1 publication
1
182
0
8
Order By: Relevance
“…In particular, use of the Internet for browsing increases the likelihood of buying through it [12]. Similarly, longer experience in buying online has a positive effect on shopping activity [60] because consumers became more confident using the Internet and perceive less risk in purchasing across multiple channels [63].…”
Section: The Role Of the Experience In Shopping Onlinementioning
confidence: 99%
“…In particular, use of the Internet for browsing increases the likelihood of buying through it [12]. Similarly, longer experience in buying online has a positive effect on shopping activity [60] because consumers became more confident using the Internet and perceive less risk in purchasing across multiple channels [63].…”
Section: The Role Of the Experience In Shopping Onlinementioning
confidence: 99%
“…The definition is similar to that proposed by (Schoenbachler & Gordon, 2002).Perceived risk is considered a multidimensional construct and measured as an overall average of six-risk dimension averages. Here, where Nis perceived risk facets and is the average of each risk type defined as , with n denoting the number of items measuring each risk.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Thereby, the literature suggests that past experience affects consumer attitudes (Fazio and Zanna, 1981 On the other hand, authors like Dholakia and Uusitalo (2002) or Schoenbachler and Gordon (2002) state that experiences or past behavior establish a powerful predictor of future actions. Furthermore, the literature proves that consumers with frequent access to Internet buy more in online channels than consumers with less frequency of use (Kwak, Fox and Zinkhan, 2002); that past experience with home shopping channels has a positive influence in the adoption of new home shopping channels (Dholakia and Uusitalo, 2002); that the satisfaction with past online purchases experiences is positively related with purchase intention on this channel (Dennis, Jayawardhena, and Papamatthaiou, 2010); and, in short, that previous use of a channel increases the probability of use this channel in the future (Dholakia, Zhao and Dholakia, 2005;Johnson, Bellman, and Lohse, 2003;Thomas and Sullivan, 2005).…”
Section: Past Experiencementioning
confidence: 99%
“…Thereby, it is becoming increasingly common to find consumers using two, three or even more channels in the same purchase process (Berman and Thelen, 2004;Schoenbachler and Gordon, 2002;Verhoef, Neslin and Vroomen, 2007). It has been demonstrated that customers using different channels in the same purchase process are more satisfied and loyal (Shankar, Smith and Rangaswamy, 2003).…”
Section: Determinants Of Multichannel Behaviormentioning
confidence: 99%